Promotion of upland rice (Oryza sativa L.) growth by endophytic bacteria isolated from Nipa Palm (Nypa fruticans) - Santos, A. J. C.; Cruz, J. A. (International Journal of Agricultural Technology, 2017)
Nitrogen and phosphorus have been identified as poorly available in the nipa palm ecosystems. Although it represents low nutrient environment, nipa can still grow efficiently and able to sustain high productivity. Possible reason is that symbiotic microbes perform mechanisms that involve conversion of atmospheric nitrogen to ammonium and nitrates that are usable by plants. In this study, five endophytic bacteria: NBor1, Enterobacter aerogenes; NBor2, Raoultella planticola; NQb2, Pectobacterium cypripedii; NAyr1, Serratia marcescens; and NAol2, Pantoea agglomerans were evaluated for their potential in enhancing the growth of upland rice under screenhouse conditions at the Applied Biology Center for the Rice Environment, Philippine Rice Research Institute. These isolates were able to produce multiple plant growth-promoting compounds such as IAA, ACC-deaminase and phosphatase. Inoculation with isolates NBor1, NBor2, and NQb2 significantly increased shoot fresh weight ranging from 73% to 89% relative to the uninoculated control. Similarly, inoculation with NBor1 and NQb2 significantly increased root fresh weight by 238.34% and 204.36%, respectively. Highest shoot dry weight (8.91 g/pot) was obtained from NBor2 inoculated plants. Inoculation with NBor1 significantly increased root length by 30.21% relative to the uninoculated treatment. Moreover, inoculation with NBor2and NAol2 significantly increased root and shoot phosphorus uptake by 94.26% and 102.73%, respectively. The efficacy of the selected endophytic bacteria in enhancing the plant growth under screenhouse conditions suggests their potential as bio-fertilizing agent for upland rice. However, field assessment should be conducted to determine the effectiveness of endophytic nitrogen-fixing bacteria under the presence of biotic and abiotic stresses.